The debtor's game : a novel - Mongeau, Isabelle (W. W. Norton & Company, 2026)
"As a palace faerie, Avery is busy preparing Lady Kassandra, a High Fae of the House of Illusion, for the upcoming coronation. Both of their freedoms rely on it: Kassandra, to escape her violent brother, and Avery, to pay off rings of debt tattoos she has inherited from her family, which force her to serve the High Fae. After a series of tragic events, Avery is forced to split her loyalties between Lady Kassandra and the newly crowned King Maxian, an alluring High Fae of staggering power. Avery agrees to spy on the King in exchange for liberating her family from debt, forming a triangle that proves more dangerous by the minute--further complicated by Avery's warring desire and resentment for both Maxian and Kassandra. But freedom from her debt grows further out of reach when she's forced to test her loyalties, leading her to uncover secrets about the High Fae with earth-shattering implications. Soon, Avery must find out whether the faeries--and herself--are really as powerless against the High Fae as they seem...or whether she just might hold the key to freeing them all." --